Respuesta :

Answer:

30 - 12x or 6(5 - 2x)

Step-by-step explanation:

Given expression:

  • 4[5 + (-3x)] + 10​

First, let us simplify the expression inside the parentheses;

  • ⇒ 4[5 + (-3x)] + 10​
  • ⇒ 4[5 - 3x] + 10​

Then, let us open the parentheses by simplifying the distributive property;

  • ⇒ 4[5 - 3x] + 10​
  • ⇒ 20 - 12x + 10​

Finally, let us simplify the expression by adding 10 to 20.

  • ⇒ 20 - 12x + 10​
  • ⇒ 30 - 12x

[Optional] Factor the expression by putting the expression in parentheses.

  • ⇒ 30 - 12x
  • ⇒ (30 - 12x)

Since 6 is divisible to all the terms in the expression, we can divide 6 to all the terms in the expression and take "6" outside the parentheses.

  • ⇒ 6(30/6 - 12x/6)
  • ⇒ 6(5 - 2x)

Therefore, the simplified expression is 30 - 12x or 6(5 - 2x).

ACCESS MORE